2012
DOI: 10.1002/emmm.201200222
|View full text |Cite
|
Sign up to set email alerts
|

TROP2 is epigenetically inactivated and modulates IGF‐1R signalling in lung adenocarcinoma

Abstract: Trop-2, a cell surface glycoprotein, contains both extracellular epidermal growth factor-like and thyroglobulin type-1 repeat domains. Low TROP2 expression was observed in lung adenocarcinoma tissues as compared with their normal counterparts. The lack of expression could be due to either the loss of heterozygosity (LOH) or hypermethylation of the CpG island DNA of TROP2 upstream promoter region as confirmed by bisulphite sequencing and methylation-specific (MS) polymerase chain reaction (PCR). 5-Aza-2′-deoxyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
126
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(133 citation statements)
references
References 47 publications
7
126
0
Order By: Relevance
“…They also exhibit better survival rates. Thus, TROP2 overexpression is an important independent marker of prognosis in lung carcinomas.A similar relationship is seen in colorectal carcinomas [4]. Decreased overall survival and increased invasiveness is seen in stage IIB colorectal carcinomas that show upregulation of TROP2.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…They also exhibit better survival rates. Thus, TROP2 overexpression is an important independent marker of prognosis in lung carcinomas.A similar relationship is seen in colorectal carcinomas [4]. Decreased overall survival and increased invasiveness is seen in stage IIB colorectal carcinomas that show upregulation of TROP2.…”
supporting
confidence: 62%
“…A similar relationship is seen in colorectal carcinomas [4]. Decreased overall survival and increased invasiveness is seen in stage IIB colorectal carcinomas that show upregulation of TROP2.…”
supporting
confidence: 62%
“…Of note, Trop-2 expression appears to discriminate populations with stem-like activity [49], which may be important for initiation and perpetuation of cancers [50,51]. A different role of Trop-2 in cancer growth has been recently reported by Lin et al [52] in lung carcinoma, where Trop-2 is epigenetically downregulated and affected by LOH, resulting in cancer progression via activation of IGF-1R signalling.…”
Section: Discussionmentioning
confidence: 99%
“…As a cell surface receptor, it can recognize specific ligands [6] and increase the level of intracellular calcium [7]. Although the biological function of Trop2 is unclear, accumulating evidence has demonstrated that its expression is elevated in various malignant tissues, whereas in human normal tissues relatively low or no Trop2 expression is observed [811].…”
Section: Introductionmentioning
confidence: 99%